Benthic macrofauna of soft-bottoms in priority coastal areas for conservation in Brazil - Neves, Raquel A. F.; Valentin, Jean L. (Arquivos de Ciências do Mar, 2011)
Macrobenthic organisms are useful indicators of estuarine environmental status as they respond predictably to many kinds of natural and human-induced disturbances. The goal of the present review is to assess the state of knowledge about these communities on priority estuaries, mangroves and coastal lagoons considered as priorities for conservation in Brazil; to compare the knowledge among Brazilian regions, and to suggest the needs for further studies. We found 136 studies published during 1950- 2010, at 33 of 61 priority areas. The most studied regions are southeast and south, Paranaguá Bay and Patos Lagoon concentrate the major number of publication in diverse subjects related to soft-bottoms macrobenthic communities. Community ecological aspects are the least studied subject, and development of further studies on this theme are crucial. Priority areas for conservation need immediate incentives to basic research, in special north and northeast regions. Mainly studies aiming to increase knowledge on local communities including taxonomic descriptions, community characterization and spatio-temporal distribution of macrobenthic species. Considering the ecological and economic importance of estuarine systems, studies aiming the knowledge of the biodiversity should be increased to aid the implementation of monitoring, recovery and conservation programs.